Expanding the Patient Pool for Rilonacept - Emma St. John, MD; Jessica R. Carey, PharmD; Tanya Wilcox, MD; John Ryan, MD; Satvik Ramakrishna, MD; Anees Daud, MD; Denise Diaz-Robles, PA-C; Adam Smith, PharmD; Kristin Cowan, CPh-T; Libo Wang, MD (JACC: Case Reports)
Recurrent pericarditis complicates 15%-30% of acute pericarditis cases despite initial anti-inflammatory treatment. The RHAPSODY trial (Study to Assess the Efficacy and Safety of Rilonacept Treatment in Participants With Recurrent Pericarditis) showed rilonacept, an interleukin-1 cytokine trap, to be an effective therapeutic option for patients with pericarditis recurrence. This case series demonstrates the utility and challenges of rilonacept use in the types of patients excluded from RHAPSODY.